Leishmania braziliensis Infection Enhances Toll-Like Receptors 2 and 4 Expression and Triggers TNF-α and IL-10 Production in Human Cutaneous Leishmaniasis - Polari, Ludmila Porto Mendes (2019)
National Institute of Health (NIH) grant AI136032. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.